Effect of Tool Pin Features on Mechanical Properties of AA7050-T7 Friction Stir Welded Joints - Singh A.; Upadhyay V.; Misra J.P. (My University, 2025)
The joint quality and efficiency in friction stir welding extensively rely on tool geometry, including tool shoulder and pin features. Present research effort aimed to investigate the effect of threaded cylindrical and combined semi-cylindrical pin cross-section (each half of different diameters) features with swept ratios (SR) of 1.01, 1.18, and 1.38, respectively, on AA7050-T7 butt-weld joint quality. Joint quality was scrutinized through tensile testing, microhardness measurements, and fractography. Impressive tensile properties were detected for the tool with 1.01 SR value. Highest average microhardness value was evaluated for weld nugget using FSW tool having 1.38 SR value followed by SR values of 1.01 and 1.18. The fracture location of tensile specimens was witnessed at the nugget zone (NZ) for defected welds using tool pins having 1.18 and 1.38 SR values. Besides, fractured surfaces were examined through a scanning electron microscope (SEM) to evaluate the experimental outcome critically. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.